21.1: Invited Paper: Development Trend of LCD Technology. (28th November 2018) - Feng, Xiang; Sun, Xiao; Zhang, Qiang; Yang, Zhaokun; Liu, Sha; Qiu, Yun; Wang, Dan
Abstract : Recent strong requirement of higher image quality for LCDs are more important than ever along with improvement of transmission technologies such as 8K TV, 5G, and so on. This paper introduces BOE's development trend of LCDs including technical element, and design trend. The impressive influences of LCD in people's modern digital live force panel makers such as BOE to ponder on the development of LCD technology. How should the LCD become more vivid and more accepted by the user? When the 8K display and the age of 5G are coming, how should LCD undertake its historical responsibility in the ecosystem of the Internet of things? The development trend of LCD through technical elements and design elements are summarized below. LCD will become more and more magnificent.